FAKTOR RISIKO RIWAYAT KELUARGA, IMT DAN LINGKAR PINGGANG DENGAN KEJADIAN DIABETES MELLITUS DI SURAKARTA - Muwakhidah Muwakhidah; Syafira Azalia Khanza; Alfina Rahmadita; Ayu Kurnia Athasya (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2023)
Risk factors for diabetes mellitus include: genetics/family history, age, diet, obesity and others. Family history and obesity are risk factors for diabetes mellitus. Data from the Surakarta Health Office found that the highest proportion of diabetes mellitus cases was found in 3 puskesmas including the Jayengan Health Center with 51.8%, Penumping Health Center 44.9% and Sibela Health Center 43.6%. The purpose of this study was to determine the risk factors for family history, BMI, waist circumference with the incidence of diabetes mellitus. This study method used a cross-sectional design with a sample of 49 diabetic patients and 49 non-diabetic mellitus patients. This study used the location of 3 health centers in Surakarta City, namely the Jayengan, Penumping and Sibela health centers. The diagnosis of DM and non-DM patients was based on the doctor's diagnosis at the puskesmas and the patient's medical records. The research instrument used questionnaires and weight scales and microtoice to measure height and metlin to measure waist circumference. Data analysis used the Chi Square test. The results showed that family history, occupation, and waist circumference were significant risk factors for DM (p < 0.001, p = 0.03, and p = < 0.001), while age, gender and BMI were not significant for DM. The need to maintain diet and physical activity so that BMI and waist circumference remain normal.